PENERAPAN PRINSIP-PRINSIP PELAYANAN PUBLIK DALAM PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK PADA KABUPATEN SIDENRENG RAPPANG - Kamaruddin Sellang; Lahibu Tuwu; Muhammad Basri (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
The main study in this research is the application of the principles of public service in the service of the electronic identity card. The population in this research that people are obtaining an identity card as 211.104orang. Samples were taken of 100 people using the formula slovin. This type of research is descriptive kuantitatif.Data collected through observation, literature, and questionnaires. The data collected are statistically processed, and then analyzed by quantitative descriptive. The results showed the effect of the application of the principles of public service to service quality electronic identity cards in Sidenreng Rappang amounted to 85.60%, including criteria for